Early-onset neonatal sepsis as a risk factor for peri-intraventricular hemorrhage in premature infants - Mariana Martins Denicol; Vanessa Bielefeldt Leotti; Cátia Rejane Soares de Soares; Juliana Balbinot Hilgert (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To assess early-onset sepsis as a risk factor of peri-intraventricular hemorrhage in premature infants born at less than or equal to 34 weeks' gestation and admitted to a neonatal intensive care unit (NICU). Methods: This retrospective cohort study included premature patients born at less than or equal to 34 weeks' gestation who were admitted to the NICU of a tertiary hospital in southern Brazil, and born from January 2017 to July 2021. Data were collected from patients' medical records. Early-onset sepsis was measured according to the presence or absence of diagnosis within the first 72 hours of life, whereas the outcome, peri-intraventricular hemorrhage, was described as the presence or absence of hemorrhage, regardless of its grade. Results: Hazard ratios were calculated using Cox regression models. A total of 487 patients were included in the study, of which 169 (34.7%) had some degree of peri-intraventricular hemorrhage. Early-onset sepsis was present in 41.6% of the cases of peri-intraventricular hemorrhage, which revealed a significant association between these variables, with increased risk of the outcome in the presence of sepsis. In the final multivariate model, the hazard ratio for early-onset sepsis was 1.52 (95% confidence interval 1.01-2.27). Conclusion: Early-onset sepsis and the use of surfactants showed to increase the occurrence of the outcome in premature children born at less than or equal to 34 weeks' gestation. Meanwhile, factors such as antenatal corticosteroids and gestational age closer to 34 weeks' gestations were found to reduce the risk of peri-intraventricular hemorrhage.